2003
DOI: 10.1603/0022-0493-96.6.1653
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oils and Microbial Pathogens for Control of Lepidopteran Pests of Sweet Corn in New England

Abstract: Vegetable and mineral oil, Beauveria bassiana (Balsamo) and Bacillus thuringiensis subsp. kurstaki Berliner were evaluated for control of Ostrinia nubilalis (Hübner) (Lepidoptera: Pyralidae), Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae) and Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) in sweet corn (Zea mays L.). Field experiments in Maine and Massachusetts during 1993 and 1994 evaluated oils and pathogens singly or in combinations, using a single application directly to the top of the sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…At Stillwater in 2003, 96% of the ears harvested from the control plots were infested while the lowest rate, 53% was achieved by application of soy oil + Bt. Our results agree with previous research (Cook et al, 2003(Cook et al, , 2004Hazzard, 2003), indicating that adding Bt to oil treatments applied to the silk channel is more effective for controlling CEW than applying oils alone. The mode of action of the oil is believed to be asphyxiation, while the Bt acts as a stomach poison.…”
Section: Infestationsupporting
confidence: 92%
See 3 more Smart Citations
“…At Stillwater in 2003, 96% of the ears harvested from the control plots were infested while the lowest rate, 53% was achieved by application of soy oil + Bt. Our results agree with previous research (Cook et al, 2003(Cook et al, , 2004Hazzard, 2003), indicating that adding Bt to oil treatments applied to the silk channel is more effective for controlling CEW than applying oils alone. The mode of action of the oil is believed to be asphyxiation, while the Bt acts as a stomach poison.…”
Section: Infestationsupporting
confidence: 92%
“…In these experiments, ears treated with an oilbased material exhibited significantly higher rates of cone-tips than untreated ears or those treated with a carrageenan-based material (Table 3). Previous research noted similar effects (Carruth, 1942;Cook et al, 2003Cook et al, , 2004Hazzard, 2003) but not to the extent found in these experiments. Even when cone-tips were evaluated, the importance of the disorder in assessing marketability was discounted (Cook et al, 2003).…”
Section: Infestationsupporting
confidence: 64%
See 2 more Smart Citations
“…While plant spray oils are effective against a range of arthropod pests, when directly compared with mineral oils, their efficacy is generally lower. When applied directly to the new silk at a rate of 0.5 ml per ear of sweet corn, mineral oil was found to reduce Helicoverpa zea numbers more than corn oil (Hazzard et al. 2003).…”
Section: Introductionmentioning
confidence: 99%